3-D CFD transient simulation of transesterification in stirred tank reactor - Mohiuddin, A. K. M.; Adeyemi, Nabeel; Muyibi, Suleyman (2013)
A transient CFD simulation was successfully carried out for waste cooking oil (WCO)transesterification in a stirred tank reactor (STR). In this work, a multi-species reaction model was simplified to simulate the reactive flow in an STR using in a multiple reference frame (MRF)approach. Average velocity fields in the STR, by a mixed flow impeller were taken using a 2-D PIV technique to calculate the turbulence and dissipation energy statistically for the numerical model. The thermo-physical properties of the reacting species were incorporated as user defined function (UDF) to implement the reaction in ANSYS FluentTM. Reaction/ flow coupling was achieved using the eddy dissipation model. The biodiesel yield predictions were fairly comparable with the experimental data. Time steps of the model are important aspects that primarily affect the solutions of the simulation.